The Dynamics of Media Landscape and Media Policy in Indonesia. (June 2019) - Sukmayadi, Vidi
Democratization in communication is the starting point for mass media in achieving a prosperous information society. However, building an ideal democratic role of media is not trouble free. The incredible pace of the development of media industry in Indonesia in the last two decades poses at least two main threats to media consumers. First, the growth of the media industry in Indonesia has been driven by capital interests that lead to media oligopoly. Second, the integration of conventional media and the internet and social media technology place our society information flow on a stranglehold. The media consolidation gives the audience an illusion of information choice without realizing that actually they are losing their rights for reliable information. Hence, an upgrade of media literacy skill and a proper media policy are needed to cope with the current fast-paced world.